The Role of Social Competence of Islamic Education Teachers in the Formation of Student Character at MAN 1 Mojokerto - Nurul Fadilah; Zahwa Machrun Nisa; Wiwin Luqna Hunaida (Yayasan Zia Salsabila, 2025)
This study examines the influence of Islamic Education (PAI) teachers’ social competence on the character development of students at MAN 1 Mojokerto. Data were collected through observation, in-depth interviews with PAI teachers, and document analysis using a qualitative approach. The findings indicate that teachers play a significant role in shaping students' character through effective communication skills, fostering positive social relationships, and demonstrating exemplary behavior. Strategies employed include role modeling, collaborative learning such as discussions on